Factors effect of knowledge sharing in corporate services at Bursa Malaysia Berhad / Noor Fatihah Mohd Zin - Mohd Zin, Noor Fatihah (Faculty of Business and Management, 2014)
This project paper titled “Factor effect of knowledge sharing in corporate services at Bursa Malaysia Berhad” is conducted as a part of the requirement needed by the Faculty of Business Management, Mara University of Technology (UiTM). The purpose of this study is to identify the relationship between factors effect of knowledge and knowledge sharing and to identify the factor that most influence knowledge sharing among employees in one of the business unit in Bursa Malaysia Berhad: Corporate Services. The factors that have an effect on knowledge sharing are trust, communication between staff, organization hierarchy, reward or appraisal and information system. Researcher chose to use descriptive research design as a method to conduct this study and survey in order to obtain the data. Data used in this research are primary and secondary data such as journals and books. Researcher also use questionnaire in order to get feedback from the employees in Corporate Services in Bursa Malaysia Berhad to attain the data. The sample size in this research is 97 respondents of employees from Bursa Malaysia Berhad. Based on reliability test, respondent demographic, frequency, Pearson correlation and multiple regressions, a clear findings and result is observed. Out of the five independent variables, trust, communication between staff, reward or appraisal and information system were found to have a positive relationship with knowledge sharing. In addition, reward or appraisal was the factor that most influence knowledge sharing in Corporate Services at Bursa Malaysia. Organization hierarchy was found not have any impact on knowledge sharing. The researcher also provides some recommendations and suggestions on strongly emphasize such factors to enhance success of knowledge sharing after analysis, findings and interpretation data is done. The conclusion of this research was the outcome from the survey analysis and findings.